If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 5 + 13x + -9 = 62 Reorder the terms: 5 + -9 + -2x + 13x = 62 Combine like terms: 5 + -9 = -4 -4 + -2x + 13x = 62 Combine like terms: -2x + 13x = 11x -4 + 11x = 62 Solving -4 + 11x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 11x = 62 + 4 Combine like terms: -4 + 4 = 0 0 + 11x = 62 + 4 11x = 62 + 4 Combine like terms: 62 + 4 = 66 11x = 66 Divide each side by '11'. x = 6 Simplifying x = 6
| x=75-5 | | 5x-x-2=x+31 | | 5x+62=9x-10 | | 5(1+c)=4(c-2) | | 4(3m+5)=2(6m+8) | | 6*8+(14-11)*4= | | 7x+10x+10+6=50 | | 8.00(4.00+x)=72.00 | | 8w^2+w+1=0 | | 2(3c-1)-3=2c+7 | | 26=3(x+3)+5 | | 5n-2n=31+5 | | 11-8x=21-15x | | 26=3(2x+1)+5 | | b+3b=28 | | -2p-5=-2p(p+1) | | a^9+6a^8b-7a^7b^2= | | 3x+1=-4x+15 | | 4+7+2rs= | | 5+2g=9 | | -3(x+5)-44=2-34 | | 5 + 2 g = 9 | | 2x+8=x-6 | | -3a+21=a | | 48-3x=15x+20 | | 5x-3=2x+27 | | 4(2x+5)=2x+2(x-5)+2(x+15)+2x | | 3x+8.1=-2x+13.9 | | 3x+(-4)=19 | | exp(x)=-1 | | 8x=5x+120 | | 4x+6=50-10x |